Surface Roughness and Surface Topography of Inconel 718 in Powder Mixed Dielectric Electrical Discharge Machining (PMEDM) - Ahmad, Said; Lajis, Mohd Amri; Abdul Haq, Reazul Haq; Tajul Arifin, Ahmad Mubarak; Abdol Rahman, Mohd Nasrull; Fu Haw, Ho; Abdullah, Haslina; hassan, Mohd Fahrul (International Journal of Integrated Engineering, 2018)
In high speed EDM, maximum material removal rate (MRR) is a desirable to increase productivity rate and reducing production cost to the need of industry. However, the surface finish of the machined surface also cannot be neglected since it related to product quality and safety factor especially when to cut difficult to machine material such Inconel 718, which is widely used in aerospace industry. Surface roughness as one of the surface integrity criteria was choose as a response in this research. High discharge current from 20A to 40A, longer pulse on-time (pulse duration) from 200Âµs to 400Âµs and the different concentration of the nano Alumina powder were selected as the main parameters, respectively. The effect of powder mixed dielectric in EDM performance in terms of surface roughness was evaluated. The dielectric circulating system known as High Performance Electrical Discharge Machine (HPEDM) was attached to the conventional EDM machine to run the experiments involving powder mixed dielectric. The experiment results shows that, the highest peak current deteriorated the surface roughness. The surface roughness, Ra was increased with the increasing of the peak current. The result also shows that an increasing of the pulse duration the surface roughness was slightly improved. It is observed that, the value of Ra was closely related to the surface topography characteristic of the machined surfaces and directly depends on the applied discharge energy. There is no improvement in surface roughness when powder additive was mixed in a dielectric fluid.